Metabolic acidosis in multi drug poisoning with antidepressants and antipsychotics - Nastaran Eizadi-Mood; Saba Dehghanzad; Ali Mohammad Sabzghabaee; Ziba Farajzadegan (Wolters Kluwer Medknow Publications, 2021)
Objective: In this study, we evaluated the predictive factors for the occurrence of metabolic acidosis in patients with multi-drug poisoning, including antidepressants (Ad)/antipsychotics (Ap). Methods: This cross-sectional study was carried out in the referral poisoning center, Khorshid University Hospital, affiliated with Isfahan University of Medical Sciences. All patients with multi-drug ingestion, including Ad/Ap, were included in the study. Patients were divided into two groups with and without metabolic acidosis. Demographic factors, time from ingestion to admission, clinical manifestations, length of hospital stay, and outcome were compared in two groups. Binary logistic regression was used to identify factors associated with the risk of metabolic acidosis occurrence. Findings: Among the 206 evaluated patients, 45 patients (21.8%) had metabolic acidosis whom the majority were female (73.3%) with intentional purposes (77.8%). 31.1% of the patients with metabolic acidosis had tachycardia on admission (P = 0.03). Among all variables, time from ingestion to admission (P = 0.02) and lengths of hospital stay (P = 0.002) were significantly different between patients with and without metabolic acidosis. Tachycardia on admission (adjusted odds ratio [OR], 2.24; 95% confidence interval [CI]: 1.05-4.76; P = 0.036) and time from ingestion to admission (adjusted OR, 1.06; 95% CI: 1.00-1.13; P = 0.04) were also the predictive factors in occurrence of metabolic acidosis. Most of the patients survived without any complications (94.6%), of whom 72.3% had no previous underlying somatic diseases (P = 0.05). Conclusion: Admission tachycardia and the time elapsed from ingestion to admission may be considered important factors for predicting metabolic acidosis in multi-drug poisoning, including Ad/Ap.